Pengaruh Sistem Rekrutmen dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada CV.Wahana Karya Jaya Mojoagung - Endang Rahayu; Agus Frianto (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2022)
This research is quantitative research with a causal approach. The population used is all permanent employees of CV.Wahana Karya Jaya Mojoagung. Sampling technique using saturated sampling with the number of samples as many as 39 employees. Data collection techniques through questionnaires that have been tested for validity and reliability. Classical assumption tests include normality tests, heteroskedasticity tests, and multicollinearity tests, coefficients of determination to determine how much influence independent variables have on dependent variables, as well as multiple linear regression analysis to test and prove research hypotheses. The results of the t (partial) test study showed that the recruitment system (X1) had a positive and significant influence on employee performance (Y) on the CV.Wahana Karya Jaya Mojoagung and the work environment (X2) have a positive and significant influence on employee performance (Y) on CV.Wahana Karya Jaya Mojoagung. The results of the F (simultaneous) test study showed the results that the recruitment system (X1) and the work environment (X2) as a whole had a simultaneous and significant effect on employee performance (Y) on the CV.Wahana Karya Jaya Mojoagung. Keywords: Recruitment system; Work environment; Employee Performance